The Aceh Governor’s Authority in Approving Regional Police Chief Appointments: An Analysis within the Unitary State Framework - Darmoyo, Suryo Sumantri; Husni, Husni; Purnama, Eddy; Zulfadli, Zulfadli (SCAD Independent, 2024)
This research aims to understand the fundamental philosophy behind the Aceh Governor’s authority in approving the appointment of the Regional Police Chief. It also aims to define and explore the concept of the Aceh Governor’s authority in approving the appointment of the Regional Police Chief within the framework of the unitary state paradigm. Finally, it seeks to identify the most effective procedure for the Aceh Governor’s approval in appointing the Regional Police Chief. This research follows a normative juridical approach, employing a statutory, conceptual, and historical method. The results of the research in this study show that the authority of the Governor of Aceh in approving the appointment of the Regional Police Chief, in accordance with the unitary state paradigm, can be attached to the provisions of Article 205 of the UUPA, which states that the appointment of the Regional Police Chief must be with the Governor’s approval, which is basically contrary to Article 18 of the 1945 Constitution, which states that regions exercise autonomy as wide as possible but are limited by government affairs regulated by law. There is no synchronization between one law and another, nor is there synchronization of legal regulations regarding the authority of the police and Wilayatul Hisbah.